α-Mangostin hydrogel film with chitosan alginate base for recurrent aphthous stomatitis (RAS) treatment: study protocol for double-blind randomized controlled trial - Vitamia, Cszahreyloren; Iftinan, Ghina Nadhifah; Latarissa, Irma Rahayu; Wilar, Gofarana; Cahyanto, Arief; Mohammed, Ahmed Fouad Abdelwahab; El-Rayyes, Ali; Wathoni, Nasrul (Frontiers in Pharmacology, 2024)
Background: Recurrent Aphthous Stomatitis (RAS) is a common ulcerative disease of the oral mucosa which is characterized by pain, and recurrent lesions in the oral cavity. This condition is quite painful, causing difficulty in eating, speaking and swallowing. Topical medications have been used for this condition, but the obstacle in using topical medications is the difficulty of achieving drug effects due to saliva wash out. This problem can be overcome by film hydrogel formulation which can protect the ulcer and reduce the pain to some extent. α-mangostin is a xanthone isolated from the rind of the mangosteen fruit. One of the activities of α-mangostin is anti-inflammatory effects, which operate through the characteristic mechanism of inhibiting the inflammatory response. This protocol study aims to investigate the efficacy of an α-mangostin hydrogel film with a chitosan